(untitled) (Journal of Oriental Studies, 2019)
The article explains the discovery and research of one of The oldest types of Chinese writing - the shell and bone inscription (JiaGu en). At the same time, based on historical facts, the article is devoted to the definition of the role of written culture in the life and development of any state and nation. Many valuable materials about the social construction and the state system of one of the oldest civilizations in China - the Kingdom of Shan, with the help of shell - bone inscriptions were revealed. It is also reported that drinking wine was a unique kind of culture that received a comprehensive national character in the Shan era, in the end, the culture of winemaking became the main reason to become a historical monument under the destruction of the Shan Kingdom. Key words: China, bone inscription, Shan Kingdom, Chinese character, Chinese civilization, history of writing, ine country, Zhou Pathology.